Plataformas digitais e direito do trabalho - Lambert, Soraya Galassi (2025)
The purpose of this research is to analyze the various issues that arise, both of a theoretical nature and related to jurisdictional pragmatics, which affect workers, whether they are employees or not, as a result of working on the business model known as “digital platforms”, also known as “platformized” or “platform companies”, with an emphasis on the Uber model. The aim is to verify the effects of new digital technologies on companies and on employment contracts, in order to demonstrate that this is a type of work that needs specific regulation, since, although it does not fully meet the requirements of articles 2 and 3 of the Consolidated Labour Statute, in order to characterize a typical employment contract, it needs to be given a minimum level of protection and social rights, in compliance with the dignity of the human person, enshrined in article 1, item III, of the Constitution of the Republic of 1988. The work also points out the transformations brought about by the implementation of new technologies, presenting critical premises about the concepts of big data, algorithms and artificial intelligence. It specifies the types of digital work platforms and their specific characteristics, modes of operation, observing the various economic activities, as well as the regulatory problems experienced by workers in these businesses. It examines the debate about the existence or not of an employment relationship within digital work platforms, analyzing the new conceptions of subordination and dependence. It discusses disputes between workers and digital platforms, considering aspects of substantive and procedural law. To this end, the hypothetical-deductive method was used, with quantitative and qualitative research into doctrine, legislation and case law on the subject.